Dispersion method of modified vanadium dioxide in hydrophilic system and slurry product thereof
By combining dry airflow pre-pulverization and wet sand milling processes with inert airflow and nonionic additives, the problems of vanadium dioxide powder refinement and dispersibility were solved, achieving the preparation of stable nanoparticles, improving the uniformity and optical properties of the slurry, and making it suitable for the field of intelligent optical windows.
Patent Information
- Application Number
- CN202511167312.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-08-20
AI Technical Summary
Existing technologies struggle to stably refine vanadium dioxide powder to below 100 nm while maintaining good dispersibility, resulting in poor uniformity and decreased optical properties of the slurry during coating and film formation. Furthermore, existing dispersant systems suffer from insufficient dispersion or mechanical contamination.
A combined process of dry airflow pre-pulverization and wet sand milling is adopted. Through inert airflow crushing and nonionic additives, the vanadium dioxide powder is initially refined and finely dispersed, avoiding mechanical media contamination and lattice distortion, and forming a stable nanoparticle dispersion.
It achieves stable refinement of vanadium dioxide powder to 50~100 nm, improves the dispersibility and uniformity of the slurry, is suitable for intelligent optical window applications, reduces production costs and increases production capacity.
Smart Images

Figure CN120984157A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of slurry preparation methods, in particular to a dispersion method of modified vanadium dioxide in a hydrophilic system and a slurry product thereof. BACKGROUND
[0002] In recent years, vanadium dioxide (VO2) materials have attracted extensive attention due to their intrinsic temperature-induced phase transition characteristics. When the ambient temperature exceeds the phase transition critical value, monoclinic VO2 (M phase) can reversibly transform into rutile VO2 (R phase), resulting in a significant change in the transmittance of infrared light and realizing dynamic regulation of solar thermal radiation. Based on this temperature-responsive optical property, VO2 exhibits great application potential in the field of intelligent optical windows.
[0003] However, there are still the following outstanding problems in the application and slurry preparation of VO2 at present: (1) The intrinsic phase transition temperature of pure monoclinic VO2 material is about 68 ℃, which is significantly higher than the comfortable temperature range of the human body, resulting in incompatibility between the temperature modulation range of infrared thermal radiation and the working temperature demand of actual application scenarios; (2) Defect treatment (bulk doping) of VO2 can significantly reduce the phase transition temperature to 25-40 ℃, which can meet the actual application requirements. However, due to the increase in material formula complexity and the harshness of process parameters, the nanometer particles are severely agglomerated (particle size can reach 5-10 μm) during the sintering preparation process, leading to rapid sedimentation of the powder in the slurry and poor uniformity, which not only greatly hinders the feasibility of slurry coating and film formation, but also significantly weakens the optical performance of the product.
[0004] Therefore, the current method for low-cost refinement of bulk-doped VO2 powder is mainly crushing and grinding. Conventional dry ball milling is difficult to independently and stably crush the powder particles to below 100 nm, and local overheating problems are prone to occur; for conventional wet ball milling, sand milling, high-pressure homogenization, etc., there is currently a lack of innovative process, which cannot stably crush the powder particles to below 100 nm while maintaining stable slurry dispersion.
[0005] The conventional ball milling has obvious limitations: it is difficult to stably break the particles to below 100 nm by dry ball milling, and the mechanical impact easily causes local overheating, leading to the inactivation of VO2 phase change; although wet ball milling can alleviate the overheating problem, it is easy to form hard agglomeration due to mechanical medium pollution or insufficient dispersion, and also cannot achieve nanoscale stable refinement. Even if the combined process of "ball milling + sand milling" is used, since the particle surface defects or agglomeration problems have been caused in the ball milling pretreatment stage, the subsequent sand milling is difficult to completely eliminate these problems, and still cannot balance the refinement below 100 nm and the long-term dispersion stability of the slurry. Therefore, the VO2 powder patent literature, such as the invention patent CN201710480000.X and the invention patent CN201710480405.3, tends to directly use pure monoclinic VO2 powder to avoid the above process difficulties, and controls the mass solid content of VO2 in the range of 2% to 5%.
[0006] In addition to powder refinement, the existing technology also has certain defects in improving the dispersion of VO2 powder. For example, the ultrasonic dispersion method disclosed in the invention patent CN201710480000.X has limited effect on slurry with high solid content, and is difficult to be applied on a large scale compared with wet milling; the invention patent application CN202310914840.8 only uses polyvinylpyrrolidone (PVP) as a single component dispersant and binder, while the invention patent application CN202411510720.2 uses a high-viscosity polycarboxylate dispersing system, and both of the dispersion systems have some deficiencies.
[0007] In view of the above problems and technical defects, there is an urgent need to develop a new type of refinement and dispersion process suitable for industrialization and expansion; the process method needs to balance the target powder with small particle size and the good dispersion of the slurry. The significant advantage of using this process is that it can flexibly select modified VO2 powder with different particle size ranges, thereby reducing costs, improving production capacity, achieving good industrial economic benefits, and promoting the wide application of VO2 nanomaterials in the field of intelligent optics. SUMMARY
[0008] The purpose of the present application is to provide a dispersion method of modified vanadium dioxide in a hydrophilic system to solve the problem of balancing the target powder with small particle size and the good dispersion of the slurry as proposed in the background art, and to disclose a slurry product obtained according to the dispersion method.
[0009] In order to solve the above technical problems, the present application provides the following technical solutions: A dispersion method of modified vanadium dioxide in a hydrophilic system, comprising the following steps: (1) Dry airflow pre-crushing: placing micron-level X-VO2 powder in an airflow crusher, introducing pre-cooled inert gas as a crushing medium, and crushing for a total time of 50 to 100 minutes to obtain a preliminary refined crushing product; (2) Initial slurry preparation: The crushed product obtained in step (1) is mixed with hydrophilic solvent S, and additive A is added at the same time. After stirring evenly, an initial slurry is formed. (3) Fine dispersion by sand milling: The initial slurry obtained in step (2) is added to the sand mill. During the sand milling process, the temperature of the initial slurry is kept at 25~30 ℃. Additives B and C are added step by step during the sand milling process. The sand milling is continued for 4~6 hours to obtain a slurry with a particle size of 50~100 nm.
[0010] Further, the inert gas mentioned in step (1) is nitrogen or argon with a purity of ≥99.9%, the temperature of the pre-cooled inert gas is 5~15 ℃, and the gas flow pressure of the inert gas is 0.5~0.8 MPa; The micron-sized X-VO2 powder is M-phase vanadium dioxide with an average particle size of 5~10 μm. X in the micron-sized X-VO2 powder is a doping element, and the doping element X is at least one of magnesium, tungsten, molybdenum, niobium, terbium, europium, boron or fluorine. Its particle size range is much larger than the target particle size of 50~100 nm.
[0011] Currently, pure monoclinic VO2 (M phase) can easily produce powder particles with a particle size of 50-100 nm. However, after bulk doping with other elements, the particle size of X-VO2 powder, such as in this invention, tends to increase significantly due to increased crystal structure defects during hydrothermal / solvothermal and sintering processes. This makes refinement modification during synthesis difficult and is expected to be costly. Therefore, this invention improves the process by performing preliminary dispersion and fine dispersion of larger-particle-size (5-10 μm) X-VO2 powder in a two-step process, achieving integrated powder refinement and related slurry preparation, thereby effectively bridging the gap between raw materials and applications.
[0012] The classifying wheel of the airflow crusher rotates at 3000~6000 rpm. After continuous crushing for 20 minutes, the machine is stopped for 5 minutes, and the total crushing time is 50~100 minutes. Using dry air jet milling as a preliminary dispersion method, larger particles with a diameter of 5~10 μm can be quickly broken up. This process drives the particles to produce a dual effect of "elastic collision" and "air shearing" through high-speed inert airflow. It is especially suitable for the preliminary processing of brittle and hard particles with a diameter of micron and above and a wide particle size distribution. Its core advantages are that the absence of mechanical medium contact avoids lattice contamination, the high-speed airflow shearing force is controllable to avoid lattice distortion caused by mechanical stress, and the low-temperature inert gas environment can remove heat in real time, effectively preventing X-VO2 from undergoing continuous phase change deactivation due to temperature rise. It is particularly suitable for the requirement of vanadium dioxide to "refine the particle size and retain the phase change function".
[0013] Furthermore, the hydrophilic solvent S includes an organic solvent and deionized water, wherein the organic solvent is a polar organic solvent and does not contain halogens, and the organic solvent is at least one selected from glycerol, propylene glycol, ethylene glycol, diethylene glycol, ethanol, diethylene glycol monomethyl ether, ethylene glycol butyl ether, trimethyl phosphate, triethyl phosphate, or triethanolamine. In the hydrophilic solvent S, the mass of deionized water is less than 10% of the mass of the organic solvent; When a small amount of deionized water is added to the organic solvent component, the overall solvent becomes macroscopically homogeneous and miscible. Furthermore, the polarity of the overall solvent is enhanced through the hydrogen bonding of water molecules. This further promotes the dissolution of the additive in the system while avoiding side reactions between water molecules and vanadium with +4 valence.
[0014] In addition, organic solvents are miscible with water in a certain proportion. The molecular structure of organic solvents is polar and does not contain halogens. They not only have good solubility for various types of additives, but also have the advantages of being environmentally friendly and less toxic compared to non-polar aromatic hydrocarbons and polar halogen solvents.
[0015] In step (2), the mass ratio of the hydrophilic solvent S to the micron-sized X-VO2 powder is 4~6:1. Within this mass ratio range, it can effectively prevent insufficient refining and dispersion caused by excessive solid content in the powder, and the solid content is significantly improved compared to the prior art. For example, the prior art represented by invention patents CN201710480000.X and CN201710480405.3 has limited ability to disperse nano-VO2, and can only achieve a low mass solid content concentration of 2%~5% in both oily and watery systems.
[0016] Furthermore, additive A comprises a reduced A1 component and a coordination A2 component; Component A1 contains at least one characteristic structure selected from amide, thioamide, sulfonyl, amino, or imino groups; component A2 contains at least one characteristic structure selected from carbon-oxygen heterocycles, imidazole rings, and nitrazole rings.
[0017] Component A1 is preferably any one of acetamide, acrylamide, urea, thiourea, thioacetamide, dimethyl sulfone, dicyandiamide, or N-hydroxysuccinimide, and the amount added each time is 0.5% to 2% of the mass of the micron-sized X-VO2 powder; Component A2 is preferably any one of 18-crown ether-6, 15-crown ether-5, 12-crown ether-4, glucose, fructose, galactose, 2-methylimidazole, 2-aminoimidazole, 1,2,4-triazole, or benzotriazole, and the amount added each time is 0.5% to 1% of the mass of the micron-sized X-VO2 powder.
[0018] Additive A (components A1 and A2) is added in a single step after dry crushing and before sand milling. Its main function is to prevent irreversible structural damage to the X-VO2 powder during subsequent grinding, thus avoiding hindered refining and poor dispersion. Specifically, the addition of additive A occurs during the transitional stage between dry crushing and grinding. At this point, good dispersibility of the material is not required; the focus is on providing pretreatment protection for subsequent grinding by pre-constructing a protective layer on the particle surface through the synergistic effect of A1 and A2. During this process, the continuous shear force from grinding may irreversibly damage the X-VO2 powder in the form of lattice distortion or oxidation phase transition. Therefore, it is necessary to add composite additive A, which consists of components A1 and A2 with different mechanisms of action.
[0019] Additives A, B, and C are a stabilizer, a dispersant, and a surface modifier, respectively. Additives A, B, and C are all non-ionic organic additives that do not contain acidic groups. This prevents charge neutralization and agglomeration after adsorption between ions and charged groups and the powder, and also avoids the reaction of acidic groups with X-VO2, which could cause corrosion and deterioration of the powder.
[0020] Furthermore, additive B is selected from any two of polyethylene glycol monooleate (PEG-MO), polyethylene glycol monolaurate (PEG-ML), fatty alcohol polyoxyethylene ether (AEO), castor oil polyoxyethylene ether (EL), octylphenol polyoxyethylene ether (OP), polyvinylpyrrolidone (PVP), Triton (TX), or phenacetin; the amount of additive B added is 20%~30% of the mass of the micron-sized X-VO2 powder. Unlike ionic dispersants, nonionic additive B, which does not contain acidic groups, interacts with X-VO2 powder and other solvents simultaneously through its hydrophilic and lipophilic polymer chains. With the help of sand milling, it breaks up agglomerates and further slows down subsequent agglomeration through steric hindrance; at the same time, it does not produce side reactions such as powder flocculation and corrosion due to the introduction of ionic and acidic groups.
[0021] Furthermore, additive C is selected from any one of the following surface modifier components: aminosilane KH-540, aminosilane KH-901, aminosilane FD-593, epoxysilane KH-561, mercaptosilane KH-590, pyrophosphate titanate coupling agent KR-38S, pyrophosphate titanate coupling agent KR-238S, or aluminum zirconium coupling agent UP-108; the components in additive C do not undergo violent hydrolysis reactions when exposed to water or moisture at room temperature. The amount of additive C added is 1.5% to 2% of the mass of the micron-sized X-VO2 powder.
[0022] Further, during the operation of step (3), additive B and additive C are added in sequence as follows: additive B is added at a constant speed during the first 2 hours of sand milling, and additive C is added at a constant speed during the remaining time of sand milling until the sand milling ends; the constant speed addition method is a peristaltic pump or a flow pump.
[0023] During the sand milling process, the order in which additives B and C are added is fixed and preferred. Additive B plays a role in the initial physical dispersion stage, suitable for slurries with larger particle sizes in the early stages of sand milling. It achieves dynamic crushing and dispersion through steric hindrance and physical adsorption. Additive C plays a role in the later chemical dispersion stage, suitable for the later stages of sand milling with smaller particle sizes. Through chemical methods, it effectively overcomes the tendency of nanoparticles to agglomerate, achieving fine dispersion.
[0024] The milling speed is 5000~6000 rpm, the initial slurry circulation rate is 100~150 mL / min, and the cumulative operation time is 4~6 hours. During the milling process, the working temperature of the intermediate slurry is maintained at 25~30℃ through liquid cooling. Due to the limitations of dry process characteristics, it is difficult to completely eliminate soft agglomerates between fine particles, and coarse particles at the tail end are easily left in the particle size distribution, affecting the subsequent dispersion effect. Wet milling can make up for this limitation: it uses the continuous shearing action of the grinding media and the synergistic effect of solvent-dispersant to further refine the residual coarse particles, while the uniform coating of the surface of the newly formed particles by the dispersant builds a stable barrier.
[0025] The present invention also provides a slurry prepared according to the above-described method for dispersing modified vanadium dioxide in a hydrophilic system.
[0026] Furthermore, the final average particle size of X-VO2 in the slurry is 50~100 nm.
[0027] The present invention has the following beneficial effects: This invention provides a highly efficient dispersion method for modified vanadium dioxide in a hydrophilic system, which includes a synergistic process of dry air jet milling and wet sand milling. Air jet milling achieves initial refinement through high-speed inert airflow, avoiding local overheating and mechanical contamination, and laying a uniform pretreatment foundation for sand milling. Subsequent sand milling, with the help of fine shearing and dispersant synergy, deeply dissociates agglomerates and stabilizes nanoparticles, ultimately achieving the preparation of a stable and highly dispersed slurry with particles smaller than 100 nm. This effectively overcomes the defects of large particle size and poor dispersibility of X-VO2 powder during slurry processing, and promotes the application of vanadium dioxide in intelligent and energy-saving optics.
[0028] The hydrophilic solvent S used in the initial dispersion of this invention not only has good solubility for various types of additives, but also has the advantages of being environmentally friendly and having low toxicity compared to non-polar aromatic hydrocarbons and polar halogen solvents.
[0029] The hydrophilic solvent S initially dispersed in this invention, in addition to the organic solvent component, enhances the overall polarity of the solvent through hydrogen bonding of water molecules after the addition of a small amount of deionized water. This further promotes the dissolution of the additive in the system while effectively avoiding side reactions between water molecules and +4 valent vanadium.
[0030] The additives A, B and C used in this invention are all non-ionic organic additives that do not contain acidic groups. They can prevent the charge neutralization and agglomeration of ions and charged groups after adsorption with the powder, and at the same time avoid the reaction of acidic groups with X-VO2 powder, which would cause the powder to corrode and deteriorate. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the dispersion process of the modified vanadium dioxide of the present invention; Figure 2 These are still photographs of the slurries prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention. Figure 3 These are the original powder particle size distribution curves used in Examples 1-3 and Comparative Examples 1-5 of the present invention; Figure 4 Comparison of particle size distribution curves of the slurries prepared in Examples 1-3 of this invention; Figure 5 The particle size distribution curves of the slurries prepared in Example 3 and Comparative Examples 1-5 of this invention are compared. Detailed Implementation The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or conditions recommended by the manufacturer. Furthermore, the raw materials and reagents used in the present invention can be obtained by purchasing commercially available raw materials or synthesizing them through traditional chemical conversion methods. Unless otherwise defined or stated, all technical and scientific terms used herein have the same meaning as those skilled in the art. The particle size distribution curves of the tungsten-doped vanadium dioxide powder used in the following specific embodiments and comparative examples are shown below. Figure 3 As shown, its average particle size is 6.5 μm.
[0032] The following description of embodiments is for illustrative purposes only and is intended to help understand the present invention. It should be noted that those skilled in the art can make several obvious modifications to the present invention without departing from its principles, and these modifications and alterations also fall within the scope of the claims.
[0033] Example 1: The tungsten-doped vanadium dioxide powder is treated as follows, with the complete process flow diagram shown below. Figure 1 As shown.
[0034] (1) Dry airflow pre-pulverization: 50 g of tungsten-doped vanadium dioxide powder was placed in an airflow crusher, and argon gas with a purity of 99.9% that had been pre-cooled to 5~15 ℃ was introduced as the crushing medium. The airflow pressure was controlled at 0.6 MPa, the classifier speed was 5000 rpm, and the crushing was carried out continuously for 20 minutes, then stopped for 5 minutes, and then continued to crush for 20 minutes, then stopped for 5 minutes. The total crushing time was 50 minutes, and the pre-refined crushed product was obtained. (2) Initial slurry preparation: The crushed product obtained in step (1) is mixed with 300 g of diethylene glycol monomethyl ether, and 1 g of acrylamide and 0.5 g of 12-crown ether-4 are added at the same time. After stirring evenly, the initial slurry is formed. (3) Fine dispersion by sand milling: The initial slurry obtained in step (2) is transferred into a sand mill, and zirconia beads with a diameter of 0.1 mm are used as the grinding medium. The sand milling speed is controlled at 5000~6000 rpm and the initial slurry circulation flow rate is 100~150 mL / min. During the sand milling process, the working temperature of the slurry is maintained at 25~30 ℃ by liquid cooling.
[0035] During the sand milling process, 2.5 g of polyethylene glycol monooleate PEG4000MO and 7.5 g of fatty alcohol polyoxyethylene ether AEO-9 were first pre-dissolved in 25 g of diethylene glycol monomethyl ether and injected into the sand mill at a constant flow rate of 17.5 g / h via a peristaltic pump for 2 hours. Subsequently, 1 g of aminosilane KH-540 was dispersed in 25 g of diethylene glycol monomethyl ether and added uniformly at a flow rate of 13 g / h. The sand milling continued for 2 hours to obtain the target slurry.
[0036] The initial slurry circulation rate in step (3) above is due to the sand mill's slurry processing mode, which uses a circulating process. The sand mill is equipped with a dedicated liquid storage device. After the slurry is discharged from the inside of the sand mill, it is transported to the liquid storage device for temporary storage through pipelines, and then pumped back into the sand mill for continuous grinding, forming a closed-loop circulation process of "grinding-discharge-temporary storage-return". This method ensures that the slurry is fully and uniformly processed during the grinding process, improving the overall grinding efficiency and material fineness.
[0037] Example 2: (1) Dry airflow pre-pulverization: 50 g of tungsten-doped vanadium dioxide powder was placed in an airflow crusher, and argon gas with a purity of 99.9% that had been pre-cooled to 5~15 ℃ was introduced as the crushing medium. The airflow pressure was controlled at 0.6 MPa, the classifier speed was 5000 rpm, and the crushing was carried out continuously for 20 minutes. Then the machine was stopped for 5 minutes. The total crushing time was 100 minutes, and the pre-refined crushed product was obtained. (2) Initial slurry preparation: The crushed product obtained in step (1) is mixed with 200 g propylene glycol, 15 g ethanol and 15 g deionized water, and 0.5 g acetamide and 0.5 g 18-crown ether-6 are added at the same time. After stirring evenly, the initial slurry is formed. (3) Fine dispersion by sand milling: The initial slurry obtained in step (2) is transferred into a sand mill, and zirconia beads with a diameter of 0.1 mm are used as the grinding medium. The sand milling speed is controlled at 5000~6000 rpm and the initial slurry circulation flow rate is 100~150 mL / min. During the sand milling process, the working temperature of the slurry is maintained at 25~30 ℃ by liquid cooling. First, 5.5 g of polyethylene glycol monooleate PEG4000MO and 7.5 g of fatty alcohol polyoxyethylene ether AEO-9 are pre-dissolved in 10 g of propylene glycol and injected into the sand mill by a peristaltic pump at a constant flow rate of 11.5 g / h. The mixture is sand milled for 2 hours. Then, 1 g of aminosilane KH-540 is dispersed in 10 g of propylene glycol and added at a constant flow rate of 5.5 g / h. The mixture is sand milled for another 2 hours to obtain the target slurry.
[0038] Example 3: (1) Dry airflow pre-pulverization: 50 g of tungsten-doped vanadium dioxide powder was placed in an airflow crusher, and argon gas with a purity of 99.9% that had been pre-cooled to 5~15℃ was introduced as the crushing medium. The airflow pressure was controlled at 0.6 MPa, the classifier speed was 5000 rpm, and the crushing was carried out continuously for 20 minutes. Then the machine was stopped for 5 minutes. The total crushing time was 100 minutes, and the pre-refined crushed product was obtained. (2) Initial slurry preparation: The crushed product obtained in step (1) is mixed with 200 g propylene glycol, 15 g ethanol and 15 g deionized water, and 0.5 g 2-methylimidazole and 0.5 g urea are added at the same time. After stirring evenly, the initial slurry is formed. (3) Fine dispersion by sand milling: The initial slurry obtained in step (2) is transferred into a sand mill, and zirconia beads with a diameter of 0.1 mm are used as the grinding medium. The sand milling speed is controlled at 5000~6000 rpm and the initial slurry circulation flow rate is 100~150 mL / min. During the sand milling process, the working temperature of the slurry is maintained at 25~30 ℃ by liquid cooling. First, 5.5 g of polyethylene glycol monolaurate PEG400ML and 7.5 g of K29 type polyvinylpyrrolidone PVP are pre-dissolved in 10 g of propylene glycol and injected into the sand mill at a constant flow rate of 11.5 g / h via a peristaltic pump. The sand milling is carried out for 2 hours. Then, 1 g of pyrophosphate titanate coupling agent KR-38S is added to 11 g of propylene glycol at a uniform flow rate of 3 g / h. The sand milling is continued for 4 hours to obtain the target slurry.
[0039] Comparative Example 1: The difference between Comparative Example 1 and Example 3 is that component A1 urea is not added.
[0040] Comparative Example 2: The difference between Comparative Example 2 and Example 3 is that component A2, 2-methylimidazole, is not added.
[0041] Comparative Example 3: The difference between Comparative Example 3 and Example 3 is that the order of adding additive B (polyethylene glycol monolaurate PEG400ML and K29 type polyvinylpyrrolidone PVP) and additive C (titanate pyrophosphate coupling agent KR-38S) was changed during the sand milling process.
[0042] Comparative Example 4: The difference between Comparative Example 4 and Example 3 is that during the sand milling process, additives B (polyethylene glycol monolaurate PEG400ML and K29 type polyvinylpyrrolidone PVP) and additives C (titanium pyrophosphate coupling agent KR-38S) were added to the slurry all at once at the beginning of the sand milling process, together with additives A (2-methylimidazole and urea).
[0043] Comparative Example 5: The difference between Comparative Example 5 and Example 3 is that it does not use dry airflow pulverization but direct sand milling.
[0044] The final slurry products include the comparative slurries obtained according to Comparative Examples 1-5. The particle size analysis equipment used in this invention is a desktop laser particle size analyzer. This device is based on the principle of laser diffraction, with a testing range of 0.02~2600 μm. It is equipped with an automatic circulating sample feeding system, an ultrasonic dispersion device, and data analysis software, enabling automatic sample dispersion, testing, and real-time acquisition and analysis of particle size distribution data. The specific comparison results of particle size and dispersion stability are shown in Table 1. Table 1: Comparison of Particle Size and Dispersion Stability of Slurry.
[0045]
[0046] Based on the detection results of the laser particle size analyzer (specific detection results are as follows) Figure 3 As shown in the figure, the average particle size of the original powders used in Examples 1-3 and Comparative Examples 1-5 was approximately 6.5 μm. The average particle size of the slurries obtained in Examples 1-3 was in the range of 50-100 nm, as shown in the specific spectra. Figure 4 As shown, the prepared slurry did not settle after 3 months of storage. Specific settling results are as follows: Figure 2 As shown.
[0047] When the pulverized product obtained by dry airflow pre-grinding before sand milling is not supplemented with additive A1 or additive A2, the final slurry prepared from... Figure 5 It can be seen that the final slurry particle size has significantly increased to 150~160 nm, and from Figure 2 Slight powder sedimentation can be observed; when the order or method of adding additives B and C is changed, from Figure 5 It can be seen that the powder particle size further increases, and from Figure 2 Significant sedimentation of the slurry can be observed. In addition, in order to reduce the number of operation steps, if dry air jet milling is not performed before fine dispersion in sand milling, the final slurry will have the largest particle size and significant sedimentation.
Claims
1. A method for dispersing modified vanadium dioxide in a hydrophilic system, characterized in that, Includes the following steps: (1) Dry airflow pre-pulverization: Micron-sized X-VO2 powder is placed in an airflow pulverizer and pre-cooled inert gas is passed through as the pulverizing medium. The total pulverization time is 50~100 minutes to obtain the pre-refined pulverized product. (2) Initial slurry preparation: The crushed product obtained in step (1) is mixed with hydrophilic solvent S, and additive A is added at the same time. After stirring evenly, an initial slurry is formed. (3) Fine dispersion by sand milling: The initial slurry obtained in step (2) is added to a sand mill. During the sand milling process, the temperature of the slurry is kept at 25~30 ℃. Additives B and C are added step by step during the sand milling process. The sand milling is continued for 4~6 hours to obtain a slurry with a particle size of 50~100 nm.
2. The method for dispersing modified vanadium dioxide in a hydrophilic system according to claim 1, characterized in that, The inert gas mentioned in step (1) is nitrogen or argon with a purity of ≥99.9%; the temperature of the pre-cooled inert gas is 5~15 ℃ and the gas flow pressure is 0.5~0.8 MPa.
3. The method for dispersing modified vanadium dioxide in a hydrophilic system according to claim 1, characterized in that, The micron-sized X-VO2 powder mentioned in step (1) is M-phase vanadium dioxide with an average particle size of 5~10 μm. X in the micron-sized X-VO2 powder is a doping element, and the doping element X is at least one of magnesium, tungsten, molybdenum, niobium, terbium, europium, boron or fluorine. The classifying wheel of the airflow crusher rotates at 3000~6000 rpm. After continuous crushing for 20 minutes, the machine is stopped for 5 minutes, and the total crushing time is 50~100 minutes.
4. The method for dispersing modified vanadium dioxide in a hydrophilic system according to claim 1, characterized in that, In step (2), the hydrophilic solvent S includes an organic solvent and deionized water, wherein the organic solvent is a polar organic solvent that does not contain halogens; In the hydrophilic solvent S, the mass of deionized water is less than 10% of the mass of the organic solvent; In step (2), the mass ratio of hydrophilic solvent S to micron-sized X-VO2 powder is 4~6:1; The organic solvent is at least one selected from glycerol, propylene glycol, ethylene glycol, diethylene glycol, ethanol, diethylene glycol monomethyl ether, ethylene glycol butyl ether, trimethyl phosphate, triethyl phosphate, or triethanolamine.
5. The method for dispersing modified vanadium dioxide in a hydrophilic system according to claim 1, characterized in that, In step (2), additive A is a combination of reduced component A1 and coordinated component A2. Component A1 is any one of acetamide, acrylamide, urea, thiourea, thioacetamide, dimethyl sulfone, dicyandiamide, or N-hydroxysuccinimide; component A2 is any one of 18-crown ether-6, 15-crown ether-5, 12-crown ether-4, glucose, fructose, galactose, 2-methylimidazole, 2-aminoimidazole, 1,2,4-triazole, or benzotriazole. The amount of component A1 added each time is 0.5% to 2% of the mass of the micron-sized X-VO2 powder, and the amount of component A2 added each time is 0.5% to 1% of the mass of the micron-sized X-VO2 powder.
6. The method for dispersing modified vanadium dioxide in a hydrophilic system according to claim 1, characterized in that, In step (3), additive B is selected from any two of polyethylene glycol monooleate, polyethylene glycol monolaurate, fatty alcohol polyoxyethylene ether, castor oil polyoxyethylene ether, octylphenol polyoxyethylene ether, polyvinylpyrrolidone, Triton or phenacetin; the amount of additive B added is 20% to 30% of the mass of the micron-sized X-VO2 powder.
7. The method for dispersing modified vanadium dioxide in a hydrophilic system according to claim 1, characterized in that, In step (3), additive C is selected from any one of the following: aminosilane KH-540, aminosilane KH-901, aminosilane FD-593, epoxysilane KH-561, mercaptosilane KH-590, pyrophosphate titanate coupling agent KR-38S, pyrophosphate titanate coupling agent KR-238S, or aluminum zirconium coupling agent UP-108 surface modifier components; The amount of additive C added is 1.5% to 2% of the mass of the micron-sized X-VO2 powder.
8. The method for dispersing modified vanadium dioxide in a hydrophilic system according to claim 1, characterized in that, In step (3) during the fine dispersion process of sand milling, additive B and additive C are added in sequence as follows: additive B is added at a constant speed during the first 2 hours of sand milling, and additive C is added at a constant speed during the remaining time of sand milling until the sand milling is completed; the constant speed addition method is a peristaltic pump or a flow pump. Additives B and C are pre-dissolved in a solvent, which is an organic solvent in a hydrophilic solvent S, before being added.
9. A slurry prepared by the method of dispersing modified vanadium dioxide in a hydrophilic system according to any one of claims 1-8.
10. The slurry according to claim 9, characterized in that, The average particle size of X-VO2 in the slurry is 50~100nm.
Citation Information
Patent Citations
A vanadium dioxide ink for inkjet printing, its preparation method and application
CN107141889B
Vanadium dioxide water-based ink for inkjet printing, its preparation method and application
CN107189550B
Preparation process and method for coating tungsten-doped vanadium dioxide nanoparticles on surface of silicon dioxide in self-adsorption mode and application of preparation process and method for coating tungsten-doped vanadium dioxide nanoparticles on surface of silicon dioxide in self-adsorption mode
CN119371112A
Preparation method and application of a kind of ball milling method-calcination process preparation cesium tungstate vanadium mixed heat insulation coating
CN119391240B
Preparation method of nano-vanadium dioxide power oily paint
CN105482539A